Information literacy via the web: a framework - N.N, Edzan; A.N, Zainab (Persatuan Pustakawan Malaysia, 2005)
Information literacy is defined as the ability to recognize when information is needed and the ability to locate, evaluate, and use effectively the needed information. The availability of massive amount of information is creating a need for education on how to evaluate and use information. Turning information into knowledge through intelligent use is critical for everyone in higher education. Institutions of higher learning have a special responsibility to prepare students for careful and informed use of information. In fulfilling this responsibility, different institutions have developed different ways of assuring information literacy competency among their students. Currently, nine public universities in Malaysia conduct some form of information literacy course for their undergraduates using the teacher-centred approach, each one labeled differently. Interestingly, all these programmes are prepared and delivered by the library staff with no collaboration from the academics. However, the programmes offered differ considerably from university to university since Malaysia does not have national information literacy competency standards for higher education to be used as a benchmark for the preparation and delivery of information literacy courses. Recent changes in higher education and the current focus on e-learning offer librarians and academics opportunities to explore the Web not only as a resource tool but also as a learning tool. This paper presents a proposal for the development of a generic template-based prototype of a Web-based information literacy course for undergraduates at the Faculty of Computer Science and Information Technology, University of Malaya with the necessary contents. Once completed the template could be used across the curriculum by all disciplines throughout the various public universities.